Long‐term zero‐tillage enhances the protection of soil carbon in tropical agriculture. (5th May 2021) - Cooper, Hannah V.; Sjögersten, Sofie; Lark, Richard M.; Girkin, Nicholas T.; Vane, Christopher H.; Calonego, Juliano C.; Rosolem, Ciro; Mooney, Sacha J.
Abstract: Contrasting tillage strategies not only affect the stability and formation of soil aggregates but also modify the concentration and thermostability of soil organic matter associated with soil aggregates. Understanding the thermostability and carbon retention ability of aggregates under different tillage systems is essential to ascertain potential terrestrial carbon storage. We characterized the concentration and thermostability of soil organic carbon (SOC) within various aggregate size classes under both zero and conventional tillage using novel Rock‐Eval pyrolysis. The nature of the pore systems was visualized and quantified by X‐ray computed tomography to link soil structure to organic carbon preservation and thermostability. Soil samples were collected from experimental fields in Botucatu, Brazil, which had been under zero‐tillage for 2, 15 and 31 years, and from adjacent fields under conventional tillage. Soils under zero‐tillage significantly increased pore connectivity whilst simultaneously decreasing interaggregate porosity, providing a potential physical mechanism for protection of SOC in the 0–20‐cm soil layer. Changes in the soil physical characteristics associated with the adoption of zero‐tillage resulted in improved aggregate formation compared to conventionally tilled soils, especially when implemented for at least 15 years. In addition, we identified a chemical change in composition of organic carbon to a more recalcitrant fraction following conversion to zero‐tillage, suggesting aggregates were accumulating rather than mineralizing SOC. These data reveal profound effects of different tillage systems upon soil structural modification, with important implications for the potential of zero‐tillage to increase carbon sequestration compared to conventional tillage. Highlights: Different tillage systems may affect SOC thermostability and C retention potentials of soil aggregates. SOC thermostability was characterised by Rock‐Eval pyrolysis and pore systems were quantified by X‐ray CT within aggregate size classes. Profound effects of zero versus conventional tillage upon soil structural modification were observed Important implications for zero‐tillage to increase C sequestration versus conventional tillage.